Student's Perception of the Effectiveness of Teacher Communication in Guiding Problem-Based Learning Projects - Hidayat, Muhammad (Persepsi: Communication Journal, 2024)
Communication between teachers and students is an important element in problem-based learning (PBL). This study aims to explore students' perceptions of the effectiveness of teacher communication in guiding PBL projects, as well as how these perceptions affect student engagement and learning outcomes. A qualitative approach with a correlational descriptive design was used to explore the relationship between teacher communication and the level of student engagement. The findings of the study show that the clarity of instruction, constructive feedback, teachers' ability to facilitate group discussions, and the use of technology have an important role in improving students' understanding and engagement in PBL. Most students assessed teacher communication as effective, but there were still challenges related to the use of technology and the involvement of all group members in discussions. The results of the correlation analysis showed a significant positive relationship between students' perception of teacher communication and their level of involvement in PBL projects, as well as contributing to better learning outcomes. This research provides insights for the development of more effective communication strategies in supporting problem-based learning, with special attention to clear instructions, relevant feedback, and appropriate use of technology.